The Influence of Problem-Based Learning Models on Mathematic Critical Thinking Ability of Students - Nani Sugiarti (JMEA : Journal of Mathematics Education and Application, 2022)
Given the importance of mathematical critical thinking skills for students in learning mathematics, it is necessary to find solutions and ways of handling them in an innovative learning process so that students can understand problems well. In learning mathematics. One model that can be applied is to apply a problem-based learning model. This study aims to examine the effect of problem-based learning models on students' mathematical critical thinking skills in social arithmetic literature. The population of this study were all seventh grade students of SMP Negeri 33 Medan spread over 8 classes. Sampling was done by rational sampling technique. One class was chosen as class V-II7 with 32 students. The sample was determined based on the relative scores of the students' initial aptitude tests. This type of research is a semi-empirical experiment with tools that test mathematical critical thinking skills. Before testing the research hypothesis, a preliminary test was conducted, namely the normality test and homogeneity test. The data from the pre-test were normally distributed and consistent. In addition, the research hypotheses were tested using analysis of covariance (ANACOVA). From the research results obtained sig ? or 0.039 0.05 then the null hypothesis is rejected, so it can be concluded that there is an effect of problem based learning learning model on students' mathematical critical thinking skills.